Model Struktural Sistem Usaha Kayu Rakyat (The Structural Model of Private Owned Timber Bussiness System) - Hardjanto . (Jurnal Manajemen Hutan Tropika, 2006)
Private owned forest in Java already exists for decades. It was initially targeted for their own consumption. Studies by Faculty of Forestry of IPB in 1976 and UGM in 1977 revealed that70% of construction timber and 90% of fuelwood was supplied by private owned forest. Since then, much attention has been paid to private owned forests in terms of forestry policy, and those privateowned forests started growing into private owned timber business (POTB) along with the growth ofits market. The POTB involved many parties, where the private owned forest farmers is the main player in the business system but has not got optimum benefit. Beside that, in the whole, theperformance of POTB system has not yet been optimal, hence strategic bussiness need to be developed. The main objective of this study was to determine POTB structural model as component in developing the business. Hence, the study used Interpretative Structural Modeling (ISM) method.The structure of POTB development system consisted of 9 elements and 86 sub elements where most of the sub elements is included in sector III, meaning there is structural problem on the whole elements. Hence, the problem will need to be solved simultaneously to develop healthy business system. In the implementation of POTB development system, it was suggested that government has to make priority of development target, based on the analysis result of the systemstructure.